The Campaign to Remove Si Kancil from Indonesian Schools (Kampanye Hapus Si Kancil dari Sekolah Indonesia) - Dipa Nugraha; Suyitno Suyitno; Elisabeth Ashton (Indonesian Language Education and Literature, 2022)
In 2010, the Indonesian Corruption Eradication Commission (KPK) declared a campaign against the most well-known trickster fable or folktale in Indonesia, Si Kancil. They urged for Si Kancil’s removal from the reading materials for young children in schools. This article aims to provide a literature review relating to the arguments over the campaign to remove or preserve Si Kancil from Indonesian schools. A comparative literature review is used to compare the arguments over trickster folktales’ impact on children and how Si Kancil was put within this context. This article concludes that Si Kancil should not have been blamed for the difficulties of eradicating corruption in Indonesia. Si Kancil can benefit the cognitive and metacognitive development of Indonesian school children. It is also suggested that Si Kancil, as an Indonesian cultural artifact, should be preserved and indeed celebrated as reading material in Indonesian schools and bedtime storytelling.Pada tahun 2010, Komisi Pemberantasan Korupsi (KPK) mendeklarasikan kampanye melawan fabel atau cerita rakyat hewan cerdik yang paling terkenal di Indonesia, Si Kancil. Si Kancil mengajarkan manipulasi dan tipu muslihat kepada anak-anak Indonesia. KPK mendesak agar Si Kancil dihapus dari bahan bacaan untuk anak-anak di sekolah. Artikel ini bertujuan memberikan kajian pustaka berkenaan dengan argumen penghapusan atau pelestarian cerita Si Kancil di sekolah. Metode tinjauan pustaka komparatif dipergunakan dalam rangka membandingkan argumen tentang dampak Si Kancil pada anak-anak. Penelitian menunjukkan bahwa seharusnya Si Kancil tidak dipersalahkan atas sulitnya pemberantasan korupsi di Indonesia. Di sisi lain, dongeng Si Kancil justru dapat bermanfaat bagi perkembangan kognitif dan metakognitif siswa di Indonesia. Malah disarankan agar Si Kancil sebagai artefak budaya Indonesia untuk dilestarikan dan dirayakan sebagai bahan bacaan di sekolah-sekolah Indonesia dan dongeng pengantar tidur.